2015
DOI: 10.1007/s12035-015-9574-7
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiation of Human Endometrial Stem Cells into Schwann Cells in Fibrin Hydrogel as 3D Culture

Abstract: Human endometrial stem cells (hEnSCs) are a new source of adult multipotent stem cells with the ability of differentiation into many cell lineages. Many stem cell sources are desirable for differentiation into Schwann cells. Schwann-like cells derived from hEnSCs may be one of the ideal alternative cell sources for Schwann cell generation. In this study, for differentiation of hEnSCs into Schwann cells, hEnSCs were induced with RA/FSK/PDGF-AA/HRG as an induction medium for 14 days. The cells were cultured in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
3
20
0
1
Order By: Relevance
“…Endometrial stromal ASCs were also shown to be capable of multi-lineage differentiation into fat, bone (confirmed with presence of osteopontin, ostenectin and alkaline phosphatase) [ 22 ], cartilage, skeletal muscle [ 23 , 24 ], and smooth muscle (expressing specific smooth muscle cell markers including alpha-smooth muscle actin (α-SMA), desmin, vinculin and calponin) [ 25 ]. Plasticity has also been shown by the trans-differentiation of endometrial stromal ASCs into neural (neural and glial lineage markers such as Nestin, NF-L, MAP2, PDGFRa, CNP, Olig2, MBP and GFAP) [ 24 , 26 ], Schwann cells (expression of S100 and P75 noted) [ 27 ], Oligodendrocytes [ 28 ], pancreatic cells (shown by secretion of insulin and markers of β cells such as PDX1, proinsulin and c-peptide) [ 29 , 30 ], urinary bladder epithelial cells (urothelium, as tested by urothelium-specific genes and proteins, uroplakin-Ia/Ib, II, III and cytokeratin 20) [ 31 ], hepatocytes (biomarkers albumin and cytokeratin 8, reduced α-fetoprotein and α-SMA expression, synthesised urea, and stored glycogen) [ 32 , 33 ], and megakaryocytes (identified by expression of CD41a and CD42b and reduction of pluripotent transcription factors Oct4 and Sox2, platelets were seen as functional as evidenced by the upregulation of CD62p expression and fibrinogen binding following thrombin stimulation), both in vitro and in animal models [ 34 , 35 ].…”
Section: Identifying Markers That Are Highly Expressed In Cells Wimentioning
confidence: 99%
“…Endometrial stromal ASCs were also shown to be capable of multi-lineage differentiation into fat, bone (confirmed with presence of osteopontin, ostenectin and alkaline phosphatase) [ 22 ], cartilage, skeletal muscle [ 23 , 24 ], and smooth muscle (expressing specific smooth muscle cell markers including alpha-smooth muscle actin (α-SMA), desmin, vinculin and calponin) [ 25 ]. Plasticity has also been shown by the trans-differentiation of endometrial stromal ASCs into neural (neural and glial lineage markers such as Nestin, NF-L, MAP2, PDGFRa, CNP, Olig2, MBP and GFAP) [ 24 , 26 ], Schwann cells (expression of S100 and P75 noted) [ 27 ], Oligodendrocytes [ 28 ], pancreatic cells (shown by secretion of insulin and markers of β cells such as PDX1, proinsulin and c-peptide) [ 29 , 30 ], urinary bladder epithelial cells (urothelium, as tested by urothelium-specific genes and proteins, uroplakin-Ia/Ib, II, III and cytokeratin 20) [ 31 ], hepatocytes (biomarkers albumin and cytokeratin 8, reduced α-fetoprotein and α-SMA expression, synthesised urea, and stored glycogen) [ 32 , 33 ], and megakaryocytes (identified by expression of CD41a and CD42b and reduction of pluripotent transcription factors Oct4 and Sox2, platelets were seen as functional as evidenced by the upregulation of CD62p expression and fibrinogen binding following thrombin stimulation), both in vitro and in animal models [ 34 , 35 ].…”
Section: Identifying Markers That Are Highly Expressed In Cells Wimentioning
confidence: 99%
“…Stem cells have important role in regenerative medicine but the viability of these cells after transplantation into injured tissue are very low, so for solving this problem, we can use materials as a vehicle for enhancement of cell viability, promotion of the nutrient diffusion, soluble factors and metabolites. Understanding of the scaffold properties is very important for production of a new functional matrix in cells can regenerate the desired tissue structures [11,36]. In the present study, we examined the influence of fibrin gel on differentiation of CJMSCs to photoreceptor like cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…It is used as a biodegradable and biocompatible injection scaffold for tissue engineering. Furthermore, it has no toxic effects and its physical properties are easily adjusted to prepare a suitable environment for photoreceptor cells [11,23,25,36]. Fibrin gel was used as a scaffold, which is biodegradable, has no cytotoxicity, and is biocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the common mesodermal lineages, endometrial MSCs may be induced to differentiate in vitro into skeletal and cardiac muscle, 86,87 insulin-producing cells 88 and the urinary epithelium 89 in the endodermic lineages and finally into neuronal cells [similar to neurolemmocytes, Schwann cells], 90,91 and dopaminergic neurons 91 in the ectodermic lineages. 28,92,93 Therefore, these cells might be used to treat affections such as cardiac disease, muscle degeneration, diabetes type 1 and neurodegenerative diseases in the future.…”
Section: Endometrium As a Source Of Mesenchymal Stem Cellsmentioning
confidence: 99%